An electrochemical DNA sensor based on polyaniline/graphene: high sensitivity to DNA sequences in a wide range1. Issue 19 (7th October 2015) - Zheng, Qing; Wu, Hao; Shen, Zongxu; Gao, Wenyu; Yu, Yu; Ma, Yuehui; Guang, Weijun; Guo, Quangui; Yan, Rui; Wang, Junzhong; Ding, Kejian
<x xml:space="preserve">Abstract</x> In the platform constructed by a polyaniline/graphene composite, double-stranded DNA, resulting from hybridization of a DNA probe, was escaping from or remaining on the sensor surface.